Zirconium in the Nuclear Industry: Eleventh International Symposium 1996
DOI: 10.1520/stp16197s
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microstructure on Ductility and Fracture Resistance of Zr-1.2Sn-1 Nb-0.4Fe Alloy

Abstract: The effect of microstructure on the ductility and fracture resistance of Zr-1.2Sn-1Nb-(0.2–0.5)Fe alloy has been studied. Different structural states of the alloy were attained by varying the iron content and working/heat treatment schedules, which comprised quenching, cold work, and anneal. The results of the tests for uniaxial tension, impact toughness, and static crack resistance as well as the electron microscope analysis of the microstructure revealed that the main structural factors governing the level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…A large number of studies have been published on the evolution of precipitates during oxidation of the zirconium alloys [3,[7][8][9][10][11][12][13]. The microstructure of the alloys was predominantly observed by various analytical methods, e.g., conventional optical microscopy, transmitted light optical microscopy, scanning electron microscopy (SEM), and transmission electron microscopy (TEM).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of studies have been published on the evolution of precipitates during oxidation of the zirconium alloys [3,[7][8][9][10][11][12][13]. The microstructure of the alloys was predominantly observed by various analytical methods, e.g., conventional optical microscopy, transmitted light optical microscopy, scanning electron microscopy (SEM), and transmission electron microscopy (TEM).…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that oxidation of precipitates is delayed compared to the zirconium matrix [14]. The effect of SPP on metallurgical properties and corrosion has been also reported [10]. The properties of these intermetallics under irradiation environment in reactor up to a high burn-up have been the subject of several investigations [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The microstructure evolution and variations in the tensile properties of Zr alloys E110 and E125 were dealt with in detail in [1,3] where it was demonstrated that the tensile properties of these alloys (also impact strength and crack resistance) are primarily governed by the degree of matrix recrystallization and texture. As distinct from zirconium binary alloys, the fracture resistance of a multicomponent alloy of the E635 type is governed by intermetallic particles [3,4]. This work deals with studying the evolution of the microstructure and tensile properties of the multicomponent alloy E635 subjected to deformation/heat treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The processability of the alloy as deformation/heat treated involving hot and cold work as well as anneals and tensile properties and performance of its finished products are in many respects governed by the microstructure that is formed at different stages of working. One of the routes to increase the toughness and ductility of the alloy finished product is to apply β -quenching from 950-1000 0 C immediately preceding the cold work operations which provides for the structure having uniformly distributed finely dispersed intermetallic particles in the recrystallized zirconium matrix [3][4][5]. The reduction schemas involving high reduction ratios used in the fabrication of thin -walled items also require a higher toughness margin of the alloy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation